2011
DOI: 10.3844/ajidsp.2011.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antibacterial Susceptibility Patterns of the Bacteria Isolated from Patients' Blood Samples over Two Periods

Abstract: Problem statement: Due to continuous changes in the frequencies and antibacterial susceptibility patterns of nosocomial pathogens, periodical surveillance of these fluctuations could help the clinicians to treat hospitalized patients more efficiently whenever empirical therapies need to be considered. This study was conducted to compare the prevalence of the bacteria recovered from bloodstream samples by Bactec 9240, over the two periods of 2001-2004 and 2005-2008 and to evaluate their antibacterial susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…Present results show that gentamycin is highly active against most gram negative and positive bacteria. These results are not in concordance with other reports which showed that vancomycin and imipenem are the highly active ones (Japoni et al, 2011). Gentamycin being the least resistant to the isolated bacteria may be due to the fact that it does not have an oral version; it is only in form of injections which reduces its abuse.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Present results show that gentamycin is highly active against most gram negative and positive bacteria. These results are not in concordance with other reports which showed that vancomycin and imipenem are the highly active ones (Japoni et al, 2011). Gentamycin being the least resistant to the isolated bacteria may be due to the fact that it does not have an oral version; it is only in form of injections which reduces its abuse.…”
Section: Discussioncontrasting
confidence: 92%
“…Gentamycin being the least resistant to the isolated bacteria may be due to the fact that it does not have an oral version; it is only in form of injections which reduces its abuse. However, it is not expected that this activity continues for a long time as it has been observed in some studies (Japoni et al, 2011) because it is cheap and readily available. The organisms were also sensitive to pefloxacin, which is not a relatively common antibiotic and thereby making it less available for abuse.The isolates show highest resistance to Augmentin which may be as a result of the drug being readily available both in tablet and injection forms and overuse/abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation